The Effect of Fly Ash and Silica Fume on the Rheology of Cement Slurries of Ordinary Portland Cement of Grade 43 and 53 - Khan, Ahmad Waqar; Kumar, Sanjay (Engineering, Technology & Applied Science Research, 2024)
Cement slurry is the medium of dispersion of coarse and fine aggregates when preparing concrete. The flow behavior of the cement slurries is governed by rheological parameters. The lower the value of these parameters is, the better the flowability and homogeneity of the cement slurry are. Static shear stress (τs), dynamic shear stress (τd), and the thixotropic index (β) are the basic rheological parameters. The effect of fly ash and silica fume on the rheology of Ordinary Portland Concrete (OPC) 43 and OPC 53 was studied by conducting tests on a coaxial rotating-type viscometer. Fly ash dosage was increased from 10% to 30% by the weight of cement in increment steps of 5% in binary and ternary mixes. Silica fume was kept constant at 5% in the ternary mixes. It was found that τs increases with fly ash in the OPC 43 but remains almost constant for the OPC 53 in both binary and ternary mixes. τd was almost constant for both the cement slurries in both binary and ternary mixes. β increases with an increase in fly ash for OPC 43 in binary and ternary slurries but decreases in OPC 53 slurries. The increment of fly ash increases the reversible built in the OPC 43 slurries, which can be broken on the application of shear. Thus, OPC 43 is a better cement from the rheological point of view in the development of various concrete mixes.